THE EFFECT OF DIRECT COMMUNICATION AND CUSTOMER REVIEWS ON CUSTOMER SATISFACTION IN ELECTRONIC SHOPPING ON TOKOPEDIA - Rada Eramina; Hapsawati Taan; Ramlan Amir Isa (Adisam Publisher, 2025)
This study aims to analyze the impact of direct communication and customer reviews on customer satisfaction at Tokopedia. A quantitative method was applied to measure the influence of the two independent variables on the dependent variable (customer satisfaction). The sampling technique used in this study was purposive sampling. The population consisted of Tokopedia users or customers across Indonesia, with a total sample of 100 respondents. Data analysis was conducted using multiple regression tests through the SPSS 27 program. The results show that: direct communication has a positive and significant effect on customer satisfaction (35.11%), and customer reviews also contribute positively and significantly to customer satisfaction (18.11%). Simultaneously, both variables exert a positive and significant influence, explaining 76.40% of the variability in customer satisfaction at Tokopedia. These findings highlight the importance of improving direct communication and encouraging positive reviews to maintain customer satisfaction and Tokopedia’s competitive position in the e-commerce market.